Glow-Up or Fade Out? The Interplay of Glutathione Soap Use with Atti-tudes Towards Colorism and Celebrity Influence among Young Profession-als - Arcinas, Myla M.; Bracamonte, Samantha Nicole R.; Deomampo, Sophia Isabelle D.; Go, Chloe Nadine D. (Future Science / FSH-PH Publications, 2025)
The growing market of glutathione products among young Filipina professionals reflects the enduring influence of colorism and celebrity-driven beauty standards in contemporary Philippine society. This study investigated the relationship between glutathione soap use and two potential influencing factors: attitudes toward colorism and celebrity endorsement-influence. An online survey was distributed to 207 young Filipina professionals (ages 22-35) residing in Metro Manila who had used glutathione soap for at least six months. Data was analyzed using descriptive statistics, Spearman's Rank Correlation, and multiple linear regression. Results showed moderate glutathione soap use (Mdn = 3), with moderate frequency (Mdn = 3) but low intensity of use (Mdn = 2). Attitudes toward colorism were moderate overall (Mdn = 3), with strong self-concept association (Mdn = 4) and moderate ratings for impression formation, affiliation, attraction, and upward mobility (Mdn = 3). Celebrity endorsement-influence was moderate (Mdn = 3), with strong perceived attractiveness (Mdn = 4) but moderate trustworthiness and expertise ratings (Mdn = 3). Neither attitudes toward colorism (ρ = -0.001, p = 0.986) nor celebrity endorsement-influence (ρ = -0.118, p = 0.089) significantly correlated with glutathione soap use. The regression model explained only 1.8% of the variance in glutathione soap use (R² = 0.018, p = 0.161). These findings suggest young Filipina professionals exercise greater agency in navigating beauty standards than previously recognized, maintaining critical distance from colorist narratives despite acknowledging their societal impact. This research provides insights for the skincare industry, public health education, and sociological understanding of evolving beauty standards in post-colonial contexts.